THE SOUTHERN EXTENT OF THE KURA-ARAXES CULTURE IN IRAN: EVIDENCE FROM GŪNESPĀN TEPE - Насери, Реза; Ханипур, Мортеза (History, Archeology and Ethnography of the Caucasus, 2026)
During the 4th millennium BC, the Kura-Arax culture emerged as an important archaeological phenomenon in the Caucasus and the Near East. Over the course of several centuries, the culture spread from Transcaucasia and northwestern Iran to southeastern Anatolia and Levant. The culture has been referred to in Iran by various names, including Yanik, Kura-Arax, and Godin IV. During archaeological excavations at Tepe Gūnespān, Malayer, in 2009, deposits containing Kura-Arax-type pottery were discovered, providing valuable insights into the final phase of this culture in the central Zagros region. Based on archaeological findings from this site, this article examines the characteristics of the Kura-Arax culture at its southernmost limit, as well as the timing and process of its decline. The results of the excavations indicate that Gūnespān was first inhabited during the Kura-Arax period, and that cultural deposits up to 250 cm thick belong to this phase. Although no architectural remains were identified due to excavation limitations, evidence suggests that this was a permanent settlement. The most distinctive feature of this culture is its gray-black burnished pottery, which can be categorized into seven groups at Gūnespān. Most of these ceramics are plain, with incised decorations being rare. The findings indicate that the gray-black burnished pottery tradition of the Kura-Araxes culture was widespread in the central Zagros region during the first half of the third millennium BCE, demonstrating its southernmost extent of influence. By the mid-third millennium BCE, painted buff ware emerged and gradually replaced the Kura-Araxes gray-black burnished pottery tradition.
Keywords: Central Zagros; Bronze Age; Kura-Araxes; gray-black burnished pottery